2020
DOI: 10.1007/s11192-020-03431-7
|View full text |Cite
|
Sign up to set email alerts
|

Studying review articles in scientometrics and beyond: a research agenda

Abstract: Review articles are an often neglected genre in scholarly communication. Though there was intense discussion about review articles in scientometrics in the 1970s and 1980s, we find less studies devoted to this genre within the last 20 years. Yet, recent discussions in other fields, such as linguistics, sociology or medicine imply that review articles are part of important debates about problems of research in academia, such as research quality or transparency. Against that background, the purpose of this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 72 publications
2
20
0
Order By: Relevance
“…Other countries with high rates of these genres, most notably the Netherlands or Denmark, are also among the top ten adopters to evidence-based medicine (ebd.). Although the "evidence-based" movement promotes and comes with a variety of knowledge generation practices, systematic reviewing remains an important cornerstone in EBM as other studies have indicated (Blümel & Schniedermann, 2020;Ojasoo et al, 2001). In that sense, the data provided here corresponds with other studies that mentioned the link between evidence-based paradigms and the emergence of systematic reviews (Timmermans & Berg, 2003;Straßheim and Kettunen 2014).…”
Section: Systematic Reviews By Countriessupporting
confidence: 78%
See 2 more Smart Citations
“…Other countries with high rates of these genres, most notably the Netherlands or Denmark, are also among the top ten adopters to evidence-based medicine (ebd.). Although the "evidence-based" movement promotes and comes with a variety of knowledge generation practices, systematic reviewing remains an important cornerstone in EBM as other studies have indicated (Blümel & Schniedermann, 2020;Ojasoo et al, 2001). In that sense, the data provided here corresponds with other studies that mentioned the link between evidence-based paradigms and the emergence of systematic reviews (Timmermans & Berg, 2003;Straßheim and Kettunen 2014).…”
Section: Systematic Reviews By Countriessupporting
confidence: 78%
“…Similar dynamics have also been observed for academic communities consenting on theories or methods (cf. Luetge, 2004;Zollman, 2007), or the role of reviews in the formation of new disciplines (Blümel, 2020).…”
Section: Citation Impact Of Systematic Reviews Prismamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our study detected an appreciable number of review articles (426 total) in addition to primary research articles that could be analyzed in future studies. A recent report by Blumel and Shniederman, based on inputs from the Conference of the International Society of Informetrics [ 76 ], proposes a broad agenda for the study of review articles. However, including such sizable numbers review articles within the framework of our current analyses would have been problematic.…”
Section: Discussionmentioning
confidence: 99%
“…In the WoS database, each item is classified into a particular "document type" category, where "review" is one. Although there is a lack of a commonly accepted definitions of review articles, the classification applied in the WoS database has been proven to be inaccurate (Blumel & Schniedermann, 2020;Harzing, 2013). In particular, this refers to a criterion where all items containing over 100 references are automatically classified as review papers.…”
Section: Research Papermentioning
confidence: 99%